Asthma Control Can Be Maintained after Fixed-Dose, Budesonide/Formoterol Combination Inhaler Therapy is Stepped Down from Medium to Low Dose - Masayuki Hojo; Tomonori Mizutani; Motoyasu Iikura; Satoshi Hirano; Nobuyuki Kobayashi; Haruhito Sugiyama (Allergology International, 2013)
Background: In cases using a budesonide/formoterol combination inhaler, many patients are started on fixed-dose treatment at 640/18 μg (4 puffs) daily, but there are no guidelines yet regarding the step-down method when control has been maintained. Methods: Patients with moderate asthma treated with either budesonide 400 μg and salmeterol 100 μg (GINA step3 group) or salmeterol/fluticasone 250 at 2 puffs (GINA step4 group) were enrolled and started on therapy of budesonide/formoterol 4 puffs. Thereafter, step-down to 2 puffs was performed if either of the following criteria was met at 8-week intervals: fractional exhaled nitric oxide (FeNO)≤28 ppb plus asthma control test (ACT) score≥22, or ACT score≥24 at 3 consecutive visits regardless of FeNO level. Thereafter, changes in ACT score, the number of acute exacerbations and reliever use, and FeNO level were monitored through 48th week. Results: Fifty-one patients, 27 in step3 group and 24 in step4 group, underwent step-down. ACT scores and the number of reliever use remained stable in both groups even after step-down. In contrast, FeNO levels increased gradually in step4 group, whereas in the step3 group they increased immediately after step-down. Step-down was considered to be safely performed because the numbers of reliever use and those of moderate or more severe exacerbations during the 48-week period has not changed significantly compared to before step-down. Conclusions: If complete control of asthma, not only of clinical symptoms but also airway inflammation, is achieved by 3-6 months of fixed-dose budesonide/formoterol 4 puffs/day, it should be possible to safely perform step-down to 2 puffs/day.